Reduksi Noise Pada Citra Menggunakan Metode Contrast Limited Adaptive Histogram Equalization - Darmawan Ginting; Magdalena Simanjuntak; Rusmin Saragih (LKP Unity Academy, 2022)
Technological developments have changed computers so that they can process various kinds of data such as sound, images, and so on. Image is a combination of points, lines, fields, and colors to create an imitation of an object, usually a physical object or a human. Even though an image is rich in information, often the image that is owned has decreased in quality, for example, contains defects or denoises. Decreasing image quality due to noise can reduce the information contained in an image. Noise is an acoustic, electrical, or electronic interference signal that is present in a system in the form of interference which is not the desired signal. Image processing that can be done by a computer consists of several types. Image quality improvement (image enhancement) is one of the fields of image processing that is quite popular. The application of image enhancement can improve the quality of the image which was initially blurred or not in accordance with the wishes of the owner for the better. One of the image enhancement methods that can be used is Contrast Limited Adaptive Histogram Equalization (CLAHE). The use of the CLAHE method can improve poor image quality by reducing noise in the image. The system is designed with the MATLAB R2014a programming application, after carrying out the testing process on several Google Maps images, it is found that the inputted